THE ROLE OF RENGALIN IN CHRONIC BRONCHITIS - Axmedov Shamshod Jamshidovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Chronic cough declines quality of life and increases risk of complications in patients with chronic obstructive pulmonary disease (COPD). Reducing cough severity and associated negative effects is important therapeutic goal in COPD. Rengalin is a release-active combination antitussive drug based on antibodies to bradykinin, to histamine and morphine. It acts at various mechanisms of cough reflex by modifying endogenous target molecules and their interaction with receptors. The drug's efficacy, as demonstrated previously in experimental and clinical studies, is mediated by specific release-activity obtained as a result of the production process.